The relationship of HESI A2RTM composite score, science and math course grades on program completion and NCLEX-RNRTM success in an associate degree nursing program. - Robert, Nicole Larissa (Relationship of HESI A2RTM Composite Score, Science & Math Course Grades on Program Completion & NCLEX-RNRTM Success in an Associate Degree Nursing Program, 2016)
It is imperative for nursing programs to admit students who can successfully complete the program and also obtain success on the NCLEX-RNRTM. Failure to admit students who can achieve success affects the students, nursing programs, academic institutions, employers, and society. The purpose of this study was to determine the relationship of the HESI A2RTM composite score and science and math course grades on program completion and NCLEX-RNRTM success in an associate degree nursing program. The study applied Albert Bandura's theory of self-efficacy including four efficacy-activated processes that influence self-efficacy beliefs: cognitive, motivational, affective, and selection as a guiding framework. This study answered six research questions using a retrospective, descriptive correlational research design using independent samples t-test and Pearson's Chi-Square test as appropriate. The setting for this study was a non-residential community college in a metropolitan city in the southeast region of the U.S. The sample consisted of 245 students who were admitted to the nursing program within a four-year period from the fall of 2009 through the fall of 2012. The results of this study revealed there was a significant relationship between the HESI A2RTM scores of the students who are successful in passing the NCLEX-RNRTM on the first attempt and the students who were not successful. There is also a significant relationship between program completion in two years and the student's pre-admit science course grade and program completion in two years and the student's HESI A2RTM composite scores.